Asymmetric facial skin viscoelasticity during climacteric aging - Piérard GE; Hermanns-Lê T; Gaspard U; Piérard-Franchimont C (Dove Medical Press, 2014)
Gérald E Piérard,1 Trinh Hermanns-Lê,1 Ulysse Gaspard,2 Claudine Piérard-Franchimont11Laboratory of Skin Bioengineering and Imaging, Department of Clinical Sciences, University of Liège, 2Department of Gynecology and Obstetrics, University Hospital of Liège, Liège, BelgiumBackground: Climacteric skin aging affects certain biophysical characteristics of facial skin. The purpose of the present study was to assess the symmetric involvement of the cheeks in this stage of the aging process.Methods: Skin viscoelasticity was compared on both cheeks in premenopausal and post-menopausal women with indoor occupational activities somewhat limiting the influence of chronic sun exposure. Eighty-four healthy women comprising 36 premenopausal women and 48 early post-menopausal women off hormone replacement therapy were enrolled in two groups. The tensile characteristics of both cheeks were tested and compared in each group. A computerized suction device equipped with a 2 mm diameter hollow probe was used to derive viscoelasticity parameters during a five-cycle procedure of 2 seconds each. Skin unfolding, intrinsic distensibility, biological elasticity, and creep extension were measured.Results: Both biological elasticity and creep extension were asymmetric on the cheeks of the post-menopausal women. In contrast, these differences were more discrete in the premenopausal women.Conclusion: Facial skin viscoelasticity appeared to be asymmetric following menopause. The possibility of asymmetry should be taken into account in future studies of the effects of hormone replacement therapy and any antiaging procedure on the face in menopausal women.Keywords: climacteric aging, biomechanics, photoaging, skin unfolding, biological elasticity, skin tensile properties